The Veblenian roots of Institutional Political Economy - Kirsten Ford (The University of Utah, Department of Economics, 2011)
The term 'Institutional Economics' has been applied to some of capitalism's strongest critics as well as its most ardent apologists. This paradox in terms has bred contradictory literature in development economics, some declaring the death of this line of thought while others herald its resurgence. In examining the roots of Institutional economics, this paper attempts to disentangle the ambiguity surrounding this label. The Institutional Political Economy of Ha-Joon Chang will then be examined as a return to Institutionalism's radical roots in development economics. Concluding remarks suggest that this approach is capable of encompassing gender as an analytical category, an extension that would improve the ability of policy makers to assess the impacts of macroeconomic policy.
Keywords: B00; B15; B25; B40; 330; History of Economic Thought; Veblen; Institutionalism; Methodology